Food Waste Factors of Urban Albanian Consumers-A Multinomial Econometric Approach - Myslym Osmani; Arben Kambo (European Scientific Journal, ESJ, 2018)
Goal of this research is to improve knowledge about food waste factors in Albanian urban homes, and recommend some policies and actions on how to reduce food waste. Data collected through face-to-face interviewing of 350 urban households in Tirana city are used. The technique of multinomial logistic model and classical regression are used. A four-dimension dependent variable approach is used, to get more consistent results. Income, size of household, number of family members employed, buying food more than needed and cooking more than needed, consumer’s concern about food waste, social status, shopping and post consumption habits, are some major waste factors. Odds and pattern effects of factors are varying according to levels of waste. To show commitment in relation with food waste, Albania should adopt international activities and initiatives, make legal improvements and foster education and awareness activities.